Kebebasan Beragama Sebagai Bagian Dari Hak Asasi Manusia - Faturohman Faturohman; Afi Nurul Febriyanti; Jihan Hidayah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Freedom of religion is still very low in Indonesia. This clearly violates human rights stipulated in Article 22 of Human Rights Law Number 39 of 1999. This research aims to show why violations of freedom of religion continue to occur or discriminatory and intolerant behavior that is often anarchic. This research uses normative juridical with qualitative approach, which means collecting and using information relevant to the research subject. For this research, the nature is descriptive analysis. Secondary data is the data source. The fact that discrimination cases continue to occur shows that the Indonesian government must make improvements and evaluations in the law enforcement sector and government apparatus, as well as provide guidance to the community.